ENHANCE PRODUCT LIFECYCLE MANAGEMENT AND PURCHASE INTENTIONS PT AVO INNOVATION AND TECHNOLOGY - Ireva Amalia Sukmasari; Alldila Nadhira Amalia Ayu Setyaning (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The fast beauty industry is characterized by rapid product innovation cycles and dynamic shifts in consumer preferences, creating challenges in product lifecycle management (PLC) and inventory control. This study aims to analyze how PT AVO Innovation and Technology (AVO), an Indonesian beauty company, manages the lifecycle of its skincare products and to identify areas for improvement in promotional and inventory strategies. A qualitative descriptive approach was employed, with data collected through semi-structured interviews involving three key informants from the Product Innovation & Development, Marketing Communication, and Sales/E-commerce divisions. The data were thematically analyzed with support from PLC, supply chain management, and consumer behavior theories. The findings reveal that AVO applies a structured lifecycle process, ranging from pre-launch internal testing, promotional campaigns at launch, sales monitoring during growth, bundling strategies at maturity, to reformulation or discontinuation at decline. However, challenges remain, including inventory buildup in slow-moving products, reliance on reactive forecasting, promotional strategies focused mainly on best-sellers, and the absence of clear discontinuation criteria. These results highlight that AVO’s competitiveness depends not only on continuous innovation but also on its ability to align lifecycle management with promotional planning and inventory control. The study emphasizes the need for data-driven forecasting, lifecycle-based promotions, and stronger cross-divisional coordination to reduce risks and sustain competitiveness in the fast beauty industry.